Pengelolaan Pembelajaran Sejarah Indonesiaberbasis Teknologi Informasi Dan Komunikasi Di Smk Negeri 3 Klaten - Listriyani, Toeti, Prof. Dr. Bambang Sumardjoko, Dr. Wafrotur Rohmah, M. M. (2017)
This study is aimed to describe about 1) lesson planning, 2) learning implementation , 3) learning evaluation of Indonesia history ICT based on students' field industrial practise in SMK Negeri 3 Klaten. The methods of this study using qualitative descriptive. The design of this study using naturalis fenomelogy. The technique of collecting data is trough obsevation, deep interview and documentation. Data analysis and data processing are done by 1) data reduction, 2) data presentation, 3) taking conclusion or verificati on. In order to get valid data, triangulation and sources data are done. It means that the same data are revealed from farios sources. The result of this study indicate that 1) the activities of the learning planning of Indonesia history ICT based in SMK Negeri 3 Klaten are basically have been done . It can be seen from the Indonesia history teachers' learning administration. 2) The learning implementation of Indonesia history ICT based in SMK Negeri 3 Klaten can be seen from many efforts that have been done by the Indonesia history teachers', which are a) learning preparation, b) learning methods, c) learning material d) learning media, and 3) The learning evaluation of Indonesia history ICT based in SMK Negeri 3 Klaten basically have been done continuously. This can be proven from the learning evaluation which is done gradually from the arrangement of a) evalution schedule, b) instrument of evaluation, c) daily evaluation, mid semester evaluation, and semester evaluation.